1, 2, 4-trichlorobenzene decomposition using non-thermal plasma technology. (22nd January 2020) - ZHU 竹, Tao 涛; ZHANG 张, Xing 星; MA 马, Mingfeng 名烽; WANG 王, Lifeng 礼锋; XUE 薛, Zeyu 泽宇; HOU 侯, Yiming 益铭; YE 叶, Zefu 泽甫; LIU 刘, Tongshen 桐珅
Abstract: Non-thermal plasma (NTP) is regarded as a potential application for environmental pollution control due to its ability to remove pollutants. As a major precursor of dioxins, the influence of the parameters of 1, 2, 4-trichlorobenzene (TCB) decomposition using NTP technology was investigated through a series of experiments, including voltage, frequency, water content, initial concentration, flow rate, and oxygen content. The experimental results show that the energy injected into the NTP system has a positive correlation to voltage and frequency. Oxygen has the greatest influence on TCB decomposition. The optimal reaction condition was at 15 kV, 1000 Hz, an initial concentration of 20 mg m −3, a flow rate of 2 l min −1, H2 O at 4%, and O2 at 0%. Under this condition, the TCB removal efficiency could reach 92%. According to the generated product backstepping, the hydroxyl radical (·OH) plays an important role in TCB decomposition due to its strong oxidation, which participates in the dechlorination and oxidation reactions as free radicals, and the possible decomposition pathway of TCB by NTP is inferred from the identified by-products. It is of great significance to investigate the influence of the parameters of TCB decomposition using NTP technology in order to provide references for industrial application.